2001
DOI: 10.1007/bf02234320
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up after ileoanal pouch procedure

Abstract: Ulcerative colitis patients after restorative proctocolectomy face a high risk of developing pouchitis. The algorithm used in this study was highly efficient in identifying patients with a secondary pouchitis who require surgical treatment and patients with chronic primary pouchitis. For the latter, long-term surveillance seems mandatory because of the risk of malignant transformation of the pouch mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
0
6

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(27 citation statements)
references
References 54 publications
3
18
0
6
Order By: Relevance
“…Acute pouchitis was more frequent (21.3%) than chronic pouchitis (4.9%), as described by others 22,24,25 . Penna et al 21 reported a cumulative risk of developing pouchitis 1, 2, 5, and 10 years after IPAA of 16%, 23%, 36%, and 46%, respectively.…”
supporting
confidence: 55%
See 2 more Smart Citations
“…Acute pouchitis was more frequent (21.3%) than chronic pouchitis (4.9%), as described by others 22,24,25 . Penna et al 21 reported a cumulative risk of developing pouchitis 1, 2, 5, and 10 years after IPAA of 16%, 23%, 36%, and 46%, respectively.…”
supporting
confidence: 55%
“…Luukkonen et al 22 found a cumulative risk of 50% at 4 years and a 7 % at 6 years. Heuschen et al 24 reported a cumulative risk of 50% of pouchitis at 8 years after IPAA. Yu et al 26 found after 10 years of follow-up an overall incidence of any complication of 48%, 50% of these due to pouchitis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of pouchitis in adult UC patients reportedly ranges between 15% and 18% during the first year after ileostomy closure, reaching 48% by the tenth postoperative year [17, 18]. The first episode is observed within 1 year after ileostomy closure in 70% of patients with pouchitis [19].…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, patients are examined 3, 6 and 12 months after IPAA, followed by annual control investigations for the next 4 years, then once every 2 years [35].…”
Section: Follow-up Investigations After Ipaamentioning
confidence: 99%